Tailoring the density of nanoflakes to enhance the hybrid battery performance of the NiS sheet array electrode. (August 2021) - Wang, Li; Lv, Xiaowei; Liu, Quanbing; Jiang, Ningyi; Zhang, Lei; Wang, Hui
Graphical abstract: Highlights: Nickel sulfide sheet-like nanoarray (NiS) electrode was formed on carbon cloth. Controllable secondary nanoflakes vertically grew on primary NiS nanosheets. High energy storage ability was achieved in the assembled NiS hybrid battery. Abstract: To produce three-dimensional (3D) low-inner-resistance electrode, nickel sulfide sheet-like nanoarray (NiS) with secondary nanoflakes vertically grown on primary nanosheets is fabricated via sulfurization of hierarchical structured Ni(OH)2 supported on carbon cloth substrate. Due to profuse exposed-edge planes, the obtained electrode exhibits remarkable hybrid properties with a highly specific capacity of 361 μA h cm −2 at 2 mA cm −2 in 3 M KOH medium, and excellent cycling stability (85 % capacitance retention after 5000 cycles). Further, the fabricated flexible and lightweight electrode is used to evaluate its performance in a solid-state flexible hybrid battery. The assembled flexible hybrid battery exhibits a high energy density of 10.97 Wh kg −1 with a power density of 54.86 W kg −1 at an operating voltage of 1.6 V. Thus, the designed NiS nanosheet arrays are considered as remarkable electrode material for energy storage applications.